Single amino acid substitution Gly186Val in AdeS restores tigecycline susceptibility of Acinetobacter baumannii. (4th February 2016) - Sun, Jun-Ren; Jeng, Wen-Yih; Perng, Cherng-Lih; Yang, Ya-Sung; Soo, Po-Chi; Chiang, Yen-Sen; Chiueh, Tzong-Shi
Abstract: Objectives: Amino acid substitutions within the AdeRS two-component system are believed to result in overexpression of the AdeABC efflux pump and extensive resistance to antibiotics in clinical Acinetobacter baumannii isolates. However, the exact amino acid substitutions in AdeRS that cause overexpression of the AdeABC efflux pump remain unclear. We elucidated the role of amino acid substitutions in AdeRS by a complementation assay in an adeRS knockout strain of A. baumannii . Methods: Five types of adeRS operon from tigecycline-resistant XDR A. baumannii (XDRAB) were cloned and introduced into the adeRS knockout strain to reverse its tigecycline susceptibility. Results: Through shuffling gene segments among those five adeRS operons and performing site-directed mutagenesis, we found that the specific amino acid substitution Gly186Val in AdeS is crucial for reducing tigecycline susceptibility of A. baumannii . Conclusions: Our result demonstrates that a critical amino acid substitution in AdeS alters the AdeABC efflux pump-mediated tigecycline resistance of A. baumannii .